PENYIDIKAN TINDAK PIDANA PENIPUAN PEREKRUTAN TENAGA KERJA INDONESIA ILEGAL OLEH KEPOLISIAN RESOR DUMAI - Purba, Andry Efra; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Lately in the town of Dumai happen fraud cases of illegal recruitment Indonesia, Dumai strategic location of the city to cross into the country of Malaysia. The situation is put to good use by the perpetrators of fraud recruitment of Indonesian workers illegal. Evidence of fraud cases of illegal recruitment of Indonesian workers seen from the data that the author got from Dumai Police that their cases handled by the Fraud and illegal recruitment of Indonesian workers. On May 4, 2011 with a report number LP / 97 / V / 2011, approximately at 11.30 the arrest of a suspect named Baharudin alias Heri Bador in the sea port of Dumai. Suspect wanted dispatched 19 workers to Malaysia, workers who want to depart the suspect does not have valid documents, the 19 migrant workers were promised jobs by the suspect.The problems discussed are the First, what are the factors that cause criminal fraud recruitment of Indonesian workers illegally in Dumai Police. Second, How is the investigation of criminal fraudulent labor recruitment by illegal Indonesian Police Dumai.The method used is empirical research, another term is sociological research is also called field research and descriptive research. In collecting the data, the type of data used in this study are primary data and secondary data, ie directly through written records and interviews with the Chief of Unit II of the Criminal Investigation Police Dumai, Act No. 39 of 2004 concerning the Placement and Protection of Indonesian Workers in the Wild State, law journals and books related to the research. The data analysis was done qualitatively and conclusions drawn deductively.From the results of research by the author Based on two cases of fraud committed touts the recruitment of Indonesian workers illegally that the investigations conducted by the police is important, but the role of the police to conduct an investigation into a fraud case the employment of illegal Indonesian yet was the maximum, because the perpetrators still a fugitive / escape and until now the perpetrators of fraud cases recruitment of Indonesian illegal workers has not been found. Keywords: Crime - Labor - Illegal